A equalização fiscal na distribuição da cota-parte do ICMS no Estado do Espírito Santo - Rezende Filho, Sérgio Fassbender de (2015)
Against a backdrop of fiscal decentralization observed in Brazil in recent decades, and economic disparity partner with municipalities with different capacities of selffinancing, as well as different demands for public services, it is urgent to investigate the effects of the main intergovernmental transfer feature, the quotations the ICMS on revenue allocation among subnational entities. For this purpose the present study aimed to analyze the transfer of quota-part of the ICMS in the State of Espírito Santo, and imposing and unattended parcels that compose it, from the point of view of fiscal equalization. Information available has been used in the last IBGE census in 2010, and the amount passed on due to the quota share of the same year ICMS and identified indicators that represent the demand for public goods and services (fiscal necessity) and capacity for storage own taxes (fiscal capacity). The analysis we used multivariate linear regression to investigate the relationship of the quota share of the ICMS, and the plots that compose it, with the variables that characterize indicators of need / fiscal capacity of municipalities. The result shows that the portion of the quotaimposing the ICMS acts in the opposite direction the idea of equalization, benefiting from more resources the municipalities that have greater capacity to finance itself. On the other hand, the autonomous portion promotes a flow of resources to those municipalities that have less capacity to finance itself by own revenues and also received fewer resources of the tax share of the quota share of the ICMS. However, the weight that imposing portion of the quota share of the ICMS has the total transfer of quota share of VAF and the absence of criteria aimed at promoting fiscal equalization in the distribution of that revenue prevent municipalities that have the greatest need and lower fiscal capacity can be met by this intergovernment transfer